(untitled) (World Science, 2019)
The article focuses upon analysis of tour performances of the Gonzalez brothers Italian opera company in provincial Ukrainian town Sumy in the beginning of the XX century. It is noted that musicians` coming was an event which was actively discussed in local press. Each performance had reviews of educative and at the same time critical character. The musical observer described vocal qualities of the artists, their technique, stage effect, orchestra sounding, emotional energy of the shows in details. Basing upon the analysis of these materials the level of touring Italian opera company, performing arts of its soloists and also an impression it produced on Sumy audience are found out. The conclusion enlightens the role of Italian opera company tour in cultural life of the chief town of a district and formation of its musical environment.